HUBUNGAN KETEPATAN PENULISAN DIAGNOSIS TERHADAP KEAKURATAN KODE DIAGNOSIS PENYAKIT SISTEM CARDIOVASCULAR DI RS LAVALETTE MALANG - Suryandari, Endang Sri Dewi Hastuti; Susanti, Natalia Nur (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
Precision of writing diagnosis of cardiovascular system diseases in Lavalette Hospital Malang by 70% with accuracy diagnosis codes by 30%. The purpose of research to determine the relationship between precision in writing diagnosis and accuracy of diagnosis codes of cardiovascular system diseases in Lavalette Hospital Malang. This research used quantitive analysis with cross sectional study approach. The population of this research is 248 medical records of cardiovascular cases. The research sample is 150 medical records with simple random sampling. The independent variable is precision in writing diagnosis of cardiovascular system diseases, while the dependent variable is accuracy of diagnosis codes of cardiovascular system diseases. The univariate test results shows the percentage precision of writing diagnosis cardiovascular system disease by 48% (72 medical records) and accuracy of diagnosis codes of cardiovascular system diseases by 30% (45 medical records). The chi square test results shows there is a relationship between precision in writing diagnosis and accuracy of diagnosis codes of cardiovascular system disease in Lavalette Hospital Malang with p value of 0.019 (<0.05). To increase the level of accuracy diagnosis codes, standarized writing guidebooks for diagnosis should be created and coders should be more careful on reading medical information in medical records.